DETERMINASI LUAS PENGUNGKAPAN INFORMASI LAPORAN TAHUNAN PERUSAHAAN GO PUBLIC DI BURSA EFEK INDONESIA - Irna Purnamasari (2020)
This research was conducted to examine the effect of profitability, Leverage, managerial ownership, and audit committee on the extent of disclosure. In this study profitability, Leverage, managerial ownership, and audit committees are each measured using Return on Assets (ROA), Debt Equity Ratio (DER), the percentage of share ownership by the board of commissioners & directors, and the number of members of the audit committee, as well as the area disclosure is measured using the Wallace Index. The population in this study are publicly listed companies listed on the Indonesia Stock Exchange in the period 2016 - 2018 as many as 688 companies. Samples were selected by cluster random sampling method and collected 207 data samples consisting of 69 companies. Hypothesis testing in this test uses Multiple Linear Regression Analysis with SPSS version 25 and a significance level of 5% (0.05). The results of the test results show that: 1) Profitability affects the area of disclosure; 2) Leverage affects the area of disclosure; 3) Managerial ownership affects the area of disclosure; 4) The audit committee influences the area of disclosure.